2015
DOI: 10.4048/jbc.2015.18.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Significance of Dual-Specificity Protein Phosphatase 4 Expression in Invasive Ductal Carcinoma of the Breast

Abstract: PurposeDual-specificity protein phosphatase 4 (DUSP4), also known as mitogen-activated protein kinase phosphatase (MKP) 2 is a member of the inducible nuclear MKP group. The role of DUSP4 in cancer development and progression appears to vary with the type of malignancy. The purpose of this study was to investigate DUSP4 expression in a case series of invasive ductal carcinoma of the breast.MethodsWe constructed tissue microarrays consisting of 16, 14, 47, and 266 cases of normal breast tissue, usual ductal hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 18 publications
1
19
0
Order By: Relevance
“…Invasive ductal carcinoma represents 70-80% of all breast cancer cases, which are responsible for the majority of breast cancer fatalities. Though great progress has been made in understanding the tumorigenesis and development of breast cancer, problems surrounding treatment of these disease persist (3). As an important approach for breast cancer treatment, chemotherapy and neoadjuvant chemotherapy have already been challenged by drug resistance, even multi-drug resistance, with the underlying mechanisms remaining unclear (4).…”
Section: Introductionmentioning
confidence: 99%
“…Invasive ductal carcinoma represents 70-80% of all breast cancer cases, which are responsible for the majority of breast cancer fatalities. Though great progress has been made in understanding the tumorigenesis and development of breast cancer, problems surrounding treatment of these disease persist (3). As an important approach for breast cancer treatment, chemotherapy and neoadjuvant chemotherapy have already been challenged by drug resistance, even multi-drug resistance, with the underlying mechanisms remaining unclear (4).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, DUSP4 acts as a tumour suppressor, with low expression associated with increased tumour grade, recurrence, and poor prognosis in breast cancer patients [ 18 , 19 ]. However, DUSP4 has also been shown to be upregulated in malignant tissues [ 16 , 20 ]. Similar to DUSP1, DUSP6 is upregulated in HER2 + carcinomas; however, little is known about its expression in normal mammary tissue [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Balko et al 27 reported that the activation of the MAPK pathway due to DUSP4 loss promotes cancer stem cell-like phenotype in basal-like breast cancer. By contrast, Kim et al 12 suggested that DUSP4 is frequently upregulated in breast malignancy and may be a marker of adverse prognosis. The effects of DUSP4 in cancer progression still remain a puzzle.…”
Section: Discussionmentioning
confidence: 92%
“… 7 9 However, there are some studies, by contrast, suggesting that the gain of DUSP4 expression plays a crucial role in cancer development and progression. 10 12 It is also interesting to note recent studies showing that DUSP4 is related to drug resistance in breast cancer patients following chemotherapy. 13 , 14 So far, the clinical significance and biological effects of DUSP4 have not been established in PTC.…”
Section: Introductionmentioning
confidence: 99%